2009
DOI: 10.1007/s11127-009-9526-8
|View full text |Cite
|
Sign up to set email alerts
|

Do high taxes lock-in capital gains? Evidence from a dual income tax system

Abstract: Capital gains realizations, Tax avoidance, Tax policy, Panel data, H24, H31,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…1985 is a reasonable choice for the start of the prereform period to ensure an almost constant capital gains tax regime for the analyses in Section 3 and 4. Demographic controls include eleven variables (see also Sodini 2009a, 2009b;Daunfeldt, Praski-Ståhlgren, and Rudholm 2010). T own t is an indicator T own is an indicator variable equal to 100 for individuals residing in towns (usually) with less than 10,000 inhabitants and equal to 0 otherwise.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…1985 is a reasonable choice for the start of the prereform period to ensure an almost constant capital gains tax regime for the analyses in Section 3 and 4. Demographic controls include eleven variables (see also Sodini 2009a, 2009b;Daunfeldt, Praski-Ståhlgren, and Rudholm 2010). T own t is an indicator T own is an indicator variable equal to 100 for individuals residing in towns (usually) with less than 10,000 inhabitants and equal to 0 otherwise.…”
Section: Datamentioning
confidence: 99%
“…However, this data set does not include information on individual income or demographic factors. Daunfeldt, Praski-Ståhlgren, and Rudholm (2010) use a comprehensive micro data set but lack identifying cross-sectional variation in capital gains tax rates between individuals during their sample period. Jacob (2010) uses two 10% random samples of all German income tax statements in 2001 and 2004 and shows that the propensity to realize capital losses (gains) increases (decreases) in the marginal (progressive) income tax rate on short-term capital gains.…”
Section: Introductionmentioning
confidence: 99%
“…High capital gains taxation also locks in capital, making key agents less willing to realize capital gains (Auten and Cordes 1991;Daunfeldt et al 2010). Experiments have shown that taxing capital gains at a high rate may prevent investors from undertaking new investments (Meade 1990), thereby impairing HIE and HGFs.…”
Section: Taxation Of Capital Incomementioning
confidence: 99%
“…For further details on the capital gains changes, see National Tax Board (2009). Recent tax incidence studies also suggest that these capital gains tax changes were of importance for realization behavior (Daunfeldt, Praski-Ståhlgren and Rudholm, 2010;Jacob, 2011 …”
mentioning
confidence: 99%